2007
DOI: 10.1104/pp.107.109876
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Symbiosis in Rice Requires an Ortholog of a Legume Common Symbiosis Gene Encoding a Ca2+/Calmodulin-Dependent Protein Kinase

Abstract: In natural ecosystems, many plants are able to establish mutually beneficial symbioses with microorganisms. Of critical importance to sustainable agriculture are the symbioses formed between more than 80% of terrestrial plants and arbuscular mycorrhizal (AM) fungi and between legumes and nitrogen-fixing rhizobial bacteria. Interestingly, the two symbioses share overlapping signaling pathways in legumes, suggesting that the evolutionarily recent root nodule symbiosis may have acquired functions from the ancient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 60 publications
6
94
0
Order By: Relevance
“…As part of our effort to address the function of nonlegume orthologs of legume genes required for root symbioses, we seek to determine whether the common symbiosis genes in legumes also are required for mycorrhizal symbioses in nonlegumes using rice (Oryza sativa) as a study model. We as well as others have demonstrated that Os-DMI3, the rice ortholog of Mt-DMI3/ Lj-CCaMK/Ps-SYM9, is required for AM symbiosis in rice and able to complement a M. truncatula dmi3 mutant (Godfroy et al, 2006;Chen et al, 2007). Two recent studies revealed that the Mt-DMI2/Ms-NORK/ Lj-SYMRK/Ps-SYM19 orthologs from the two actinorhizal plants, Casuarina glauca and Datisca glomerata, are Figure 1.…”
mentioning
confidence: 83%
“…As part of our effort to address the function of nonlegume orthologs of legume genes required for root symbioses, we seek to determine whether the common symbiosis genes in legumes also are required for mycorrhizal symbioses in nonlegumes using rice (Oryza sativa) as a study model. We as well as others have demonstrated that Os-DMI3, the rice ortholog of Mt-DMI3/ Lj-CCaMK/Ps-SYM9, is required for AM symbiosis in rice and able to complement a M. truncatula dmi3 mutant (Godfroy et al, 2006;Chen et al, 2007). Two recent studies revealed that the Mt-DMI2/Ms-NORK/ Lj-SYMRK/Ps-SYM19 orthologs from the two actinorhizal plants, Casuarina glauca and Datisca glomerata, are Figure 1.…”
mentioning
confidence: 83%
“…Subsequent work showed that the AM-related function of CCaMK and its expression in flowers are conserved in rice (Oryza sativa) [29,30]. The function of CCaMK in symbiosis is thought to be the decoding of a calcium signal (calcium spiking) in root cells that have perceived AM fungal or rhizobial signals (reviewed in [6]).…”
Section: Roots and Flowers: Closer Than Apples And Oranges?mentioning
confidence: 99%
“…Legume CCaMK is a key player in the coordinated induction of infection thread formation and nodule organogenesis (7), providing fixed nitrogen in exchange for plant photosynthates as energy (5,8). Orthologs of CSP genes, including CCaMK, are also well conserved in nonleguminous plants (9,10). The Oryza sativa CCaMK (OsCCaMK) genes were strongly expressed in the roots of field-grown rice at the vegetative and reproductive stages (11); such expression is required for mycorrhization (9,12).…”
mentioning
confidence: 99%